Glioma Subtypes Based on the Activity Changes of Immunologic and Hallmark Gene Sets in Cancer - Chen, Sihan (Frontiers in Endocrinology, 2022)
Purpose: Glioma is the most common primary cranial brain tumor that arises from the canceration of glial cells (which can be in the brain or spinal cord). It is due to innate genetic risk factors or induced by a carcinogenic environment. If left untreated, the disease has a poor prognosis. Methods: In this study, we downloaded glioma data from TCGA database and GEO (GSE4412). The GSEA database was used to screen tumor microenvironment-related gene sets. Cancer subtypes were classified by GSVA enrichment method. Results: By GSVA enrichment analysis, we obtain three Gliomas cancer subtypes. After further survival prognosis analysis and biological function analysis, we obtained 13 tumor microenvironment gene sets and 14 core genes that affect patients' survival prognosis, and these genes have the potential to become targets for targeted therapies and disease detection. Conclusion: We screened a total of 13 gene sets through a series of enrichment analyses, statistical and prognostic analyses, etc. Among them, 14 core genes were identified, namely: TOP2A、TPX2、BUB1、AURKB、AURKA、CDK1、BUB1B、CCNA2、CCNB2、CDCA8、CDC20、KIF11、KIF20A and KIF2C.